Pre-hospital cardiac arrest in Prague, Czech Republic--the Utstein-style report - Franek, Ondrej; Pokorna, Milana; Sukupova, Petra (Resuscitation, 2010)
OBJECTIVE: This study aimed to report results of pre-hospital cardiopulmonary resuscitation (CPR) in the city of Prague in accordance with 'Utstein-style' recommendations. MATERIALS AND METHODS: This is a prospective study of out-of-hospital cardiac arrest (OHCA) survival in the city of Prague treated by emergency medical service (EMS). EMS Prague is a typical municipal, two-tiered ambulance service, based on the presence of a physician on the scene in all life-threatening emergencies, especially in cardiac arrests, serious breathing problems, chest-pain cases, seizures, serious trauma, etc. Since 2002, all cases of OHCA CPRs performed by EMS Prague ambulance crew are evaluated in accordance with 'Utstein-style' recommendations, including hospital-outcome score as measured by Cerebral Performance Categories (CPCs). RESULTS: In 2008, our ambulance crew performed 493 CPRs. Return of spontaneous circulation (ROSC) was achieved in 278 cases (56.3%), survival of the event in 211 cases (42.8%) and survival to hospital discharge with good neurological outcome (CPC 1 or 2) in 74 cases (15.0%). Appropriate figures for patients with first shockable rhythm (n=146) were 106 (72.6%) for ROSC, 91 (62.3%) for survived event and 51 (34.9%) for survival to discharge with good neurological outcome. Pre-hospital CPR incidence was 41.1 per 100,000 inhabitants. The majority of cases had a cardiac origin (363, 73.6%). The physician attending the arrest declared the reason unknown in 40 cases (8.1%), as a respiratory disease in 20 cases (4.1%) and in 36 cases (7.3%) the arrest was a result of trauma, drowning or poisoning.
Keywords: dospělí; směrnice jako téma; hodnocení rizik; Female; kardiopulmonální resuscitace; dítě; předškolní dítě; Urban Population; Age Factors; Needs Assessment; Cause of Death; Adult; ženské pohlaví; mladý dospělý; urgentní zdravotnické služby; odhad potřeb; Adolescent; Quality of Health Care; Cardiopulmonary Resuscitation; věkové faktory; lidé; Survival Analysis; Heart Arrest; Emergency Medical Services; Aged, 80 and over; Risk Assessment; kohortové studie; Sex Factors; Cohort Studies; prospektivní studie; Guidelines as Topic; Male; Aged; sexuální faktory; srdeční zástava; Czech Republic; Prospective Studies; Child, Preschool; městské obyvatelstvo; Young Adult; analýza přežití; Česká republika; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; příčina smrti; Middle Aged; mladiství; kvalita zdravotní péče; Humans